THE IMPORTANCE OF CLEANLINESS AND HYGIENE IN THE KITCHEN AT TREE TOP RESTAURANT LABUAN BAJO - Zakharia, Friend; Dhone, Maria (PT. Hafasy Dwi Nawasena, 2025)
This study examines how hygiene and sanitation practices shape food quality and guest satisfaction at a tourism-driven restaurant in Labuan Bajo, Indonesia. Using a qualitative descriptive design, we triangulated sources and methods through structured observations of kitchen and dining areas, in-depth interviews with food handlers and guests, and review of internal checklists and records. Data were processed with analytical cycle of reduction, display, and conclusion verification. Results indicate strong awareness yet uneven adherence to personal hygiene protocols (handwashing, clean uniforms, hair restraint) and routine equipment sanitation (scrape–soak–wash–rinse–sanitize–dry). Inconsistencies during ingredient sorting, final plating checks, and environmental control produced vulnerabilities, including sporadic contamination events. Environmental sanitation gaps centered on pest ingress routes and suboptimal waste segregation and storage. Recommendations include codifying HACCP-aligned Sanitation Standard Operating Procedures, competency-based periodic retraining, intensified supervisory observations with rapid corrective actions, and scheduled audits with KPI dashboards. Strategically, robust hygiene–sanitation systems protect public health, reinforce customer trust, and stabilize revenue while mitigating legal exposure and reputational risk. The study contributes operational evidence that hygiene and sanitation are not merely technical requirements but essential governance levers for service quality and competitiveness in foodservice operations within tourism ecosystems. Future work should quantify outcomes with longitudinal monitoring.